Contribution to the ethnobotanical and phytochemical study of Zanthoxylum zanthoxyloides (Lam.) Waterman (Rutaceae) from Mali - Cissé, Salimatou; Somboro, Aimé Anin; Cissé, Mody; Bouaré, Sékou; Tangara, Ousmane; Dembélé, Niaboula; Samaké, Drissa; Togola, Issiaka (Journal of Drug Delivery and Therapeutics, 2022)
Zanthoxylum zanthoxyloides (Lam.) Waterman (Rutaceae) is a tree from 5 to 15 m high that grows spontaneously in West Africa. It is frequently used in Malian traditional medicine for the treatment of various ailments. Thus, the present work is part of the development of this plant through an ethnobotanical survey and a phytochemical study of its leaves, stems and roots collected in Yanfolila and Ouélessébougou. The ethnobotanical survey showed that this species is used in the treatment of various pathologies such as tooth decay, toothache, throat, stomach and headaches, sickle cell anemia, sterility, cardiovascular diseases, edema, childbirth pains, and other diseases, sexual impotence, malaria, bilharzia, diabetes, hemorrhoids, dermatosis, constipation, fever, eye infections, dysentery. In most cases the preparation is done by decoction. The phytochemical screening showed the presence of coumarins, sterols and terpenes in the three investigated organs from the two sites. The alkaloids have been found in the roots and in the stems; the mucilages in all parts except in the roots of Yanfolila. The tannins are present everywhere except in the roots and in the stems of Yanfolila; flavonoids are present everywhere except in the stems of Yanfolila. The richness of the powder of these different organs in mineral elements such as calcium, iron, magnesium, sodium, potassium and copper was also highlighted.Keywords: Zanthoxylum zanthoxyloides, ethnobotanical survey, phytochemistry, mineral elements